2017
DOI: 10.1161/jaha.117.006565
|View full text |Cite
|
Sign up to set email alerts
|

Haptoglobin 2‐2 Phenotype Is Associated With Increased Acute Kidney Injury After Elective Cardiac Surgery in Patients With Diabetes Mellitus

Abstract: BackgroundRecent studies reported an association between the 2‐2 phenotype of haptoglobin (Hp 2‐2) and increased cardiorenal morbidity in nonsurgical diabetic patients. Our goal was to determine whether the Hp 2‐2 phenotype was associated with acute kidney injury (AKI) after elective cardiac surgery in patients with diabetes mellitus.Methods and ResultsWe prospectively enrolled 99 diabetic patients requiring elective cardiac surgery with cardiopulmonary bypass. Haptoglobin phenotypes were determined by gel ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 63 publications
0
14
0
Order By: Relevance
“…The diagnosis of AKI is based on two functional markers, an increase of serum creatinine and a reduction of urinary excretion. Predictors of perioperative AKI in patients undergoing heart surgery include preoperative creatinine level, endstage renal disease, 2-2 phenotype of haptoglobin, advanced age, diabetes mellitus, congestive heart failure, generalized atherosclerosis, cardiovascular collapse, nitric oxide, cyanotic heart disease, duration of surgery and elevated postoperative lactate level [4][5][6][7][8][9]. In patients with severe AKI, oliguria and fluid accumulation, renal replacement therapy is the basic method of treatment [10].…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis of AKI is based on two functional markers, an increase of serum creatinine and a reduction of urinary excretion. Predictors of perioperative AKI in patients undergoing heart surgery include preoperative creatinine level, endstage renal disease, 2-2 phenotype of haptoglobin, advanced age, diabetes mellitus, congestive heart failure, generalized atherosclerosis, cardiovascular collapse, nitric oxide, cyanotic heart disease, duration of surgery and elevated postoperative lactate level [4][5][6][7][8][9]. In patients with severe AKI, oliguria and fluid accumulation, renal replacement therapy is the basic method of treatment [10].…”
Section: Introductionmentioning
confidence: 99%
“…Hamdy et al, [41] reported that haptoglobin phenotype as a risk factor for coronary artery diseases and cardiovascular diseases in type 2 diabetes. Also, Feng et al, [42] reported that haptoglobin 2-2 phenotype is associated with increase acute kidney injury in patients with diabetes mellitus. This study is in accordance with the work of Olaniyan et al, [43] that reported higher level of haptoglobin in Nigeria type 2 diabetes due there was a high frequency of Hp 2-2 allele gene genotype which led to vascular complications.…”
Section: Discussionmentioning
confidence: 99%
“…The main strength of the current work is its transethnic design with inclusion (33,34). Unfortunately, data on these two variables were not available in both cohorts.…”
Section: Discussionmentioning
confidence: 99%